ANALISIS KINERJA BPSPAMS TIRTO SUMBER MULYO SEBAGAI PERTIMBANGAN MENJADI UNIT BUMDES DI DESA MIJEN KECAMATAN KEBONAGUNG KABUPATEN DEMAK - Astohar Astohar; Dhian Andanarini Minar Savitri; Yuyun Ristianawati; Prihansantyo Siswo Nugroho (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
BPSPAMS Tirto Sumber Mulyo Mijen Village is one of the BPSPAMS in the District Kebonagung which has the task of managing water and sanitation at the village level. In the management of water and sanitation facilities at the village level it is necessary to assess the performance so that it can be evaluated for future follow-ups for the strategy or position of the management group that has been included in the BUMDes  Maju Lancar unit. This performance appraisal standard uses the performance appraisal standard from the 2020 Technical Guidelines for SPAMS Management. The results of the performance appraisal show that in general the performance of BPSPAMS Tirto Sumber Mulyo is in the medium category. Partially, it shows the performance of planning in the low category, in the high-performance administration and finance, on the performance of drinking water and sanitation services in the medium category and for the performance of the partnership in the low category. The hope in the future for improving the performance of BPSPAMS together with BUMDes Maju Lancar needs to collaborate or increase cooperation with external parties such as academics, practitioners and government institutions that can increase benefits and benefits for the public